The Issue of Teenage Girl Marriage in Indonesian Films: Analysis of the "Yuni" Film Reception - Estavita Chantik Pembayun; Mashita Phitaloka Fandia Purwaningtyas (LONTAR: Jurnal Ilmu Komunikasi, 2022)
The film titled “Yuni” talks about a young girl named Yuni who experiences pressure from her society to get married. Despite gaining international recognition through awards at prestigious events, this film has attracted various discourses on social media. This research aims to examine the audience’s meaning of the film “Yuni”, especially for women who have married in their teens. This is phenomenological research that focuses on the experience of the audience as individuals. The research method uses Stuart Hall’s reception analysis with the concept of encoding and decoding and uses the stereotype concept of Richard Dyer as an analytical tool. This research uses in-depth interviews, observations, and literature studies. The results show that the audience’s meaning is in a position of dominance and negotiation. A dominant position occurs through scenes that show that married teenage girls are victims of a still-strong cycle of patriarchal systems and we will limit the options to develop themselves for experience after marriage. The negotiating position occurs in scenes that show stereotypes related to women must be smart in matters of kitchens, wells, and beds.